FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMAKAIAN KONTRASEPSI TUBEKTOMI PADA WANITA PASANGAN USIA SUBUR DI RSUD Dr PIRNGADI MEDAN TAHUN 2012 - Herlinawati .; Maya Fitria; Heru Santosa (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Tubectomy contraception is cutting action the fallopian/uterine tube.  Tubectomy is medical treatment by blocking uterine tube with the certain purpose to not to have a child for a long time until  for a lifetime. The number of female sterilization user in Indonesia in 2012 amounted 1.04% (Lusiana, 2012). Data from the National Population and family planning in 2012 the number of participants tubectomy is in North Sumatra as much as 8.38%. Existing participant data tubectomy at Dr. Pirngadi Local General Hospital in the period January to October 2012 was 45%. This study aimed to examine the relationship between the factors related to tubectomy contraception use among women of fertile age couples. This research was descriptive analytic study using a cross sectional approach where the measurement or observation of the subject was done in a single observation. The sample size in this study was as much as 86 respondents with a total population of 255 respondents. Data were collected through questionnaire-based interviews. Data analysis used chi square test. The results of this study showed that 58.1% of respondents used tubectomy contraception.  There were no relationship between age (p = 0.152), education (p = 0.498),  occupation (p = 0.103), knowledge (p = 0.397), culture/belief  (p = 0.714) and tubectomy contraception use among  woman of fertile age couples. There were relationship between parity (p = 0,001), attitude (p = 0.016), family support (p = 0,001) and  tubectomy contraception use among woman of fertile age couples. The health workers and Family Planning Field Workers are expected to play an active role in increasing the awareness of fertile age couples by providing a sustainable extension to the community in order to increase their participation in using tubectomy. Keywords: Family Planning Acceptor, Tubectomy Contraception